Catalytic SO2 oxidation in a periodically operated trickle-bed reactor - Lee, JK; Ferrero, S; Hudgins, RR; Silveston, PL (WILEY-BLACKWELL, 1996)
Centaur(TM) carbon (Calgon Carbon Corp.) was used as a catalyst for SO2 oxidation in a trickle bed under periodic interruption of its liquid flow for cycle periods from 15 to 60 min, cycle splits (split being the proportion of a cycle in which liquid flows) from 0.0083 to 0.2, and feed temperatures about 80 degrees C. SO2 removal in the trickle bed was improved at longer periods. At a fixed period of 15 min, a maximum occurred with split. At high splits, platinized and unplatinized carbons performed indistinguishably. Results suggested kinetic rate control at low splits and oxygen mass transport control at high splits.
Keywords: CARBON